Impact of age and breast thickness on mean glandular dose of standard digital mammography and digital breast tomosynthesis - Mohd Norsuddin, Norhashimah; Go, Justine Mei Sin; Ravintaran, Rathieswari; Arasaratnam, Shantini; Abdul Karim, Muhammad Khalis (Elsevier, 2023)
This study compares the mean glandular dose (MGD) across 2D, 3D projection and Contrast-Enhanced Digital Mammography (CEDM) mammographic techniques. The important metadata were extracted from the digital mammography console. 650 subjects were clustered based on projections, age and CBT. The MGD of 2D, 3D, and CEDM was positively correlated with CBT but inversely correlated with the age factor. This study indicate MGD of CEDM was 16 and 22 lower compared to 2D and 3D techniques, respectively.